Solvothermal synthesis and characterizations of graphene-ZnBi12O20 nanocomposites for visible-light driven photocatalytic applications. Issue 11 (1st August 2020) - Muthukrishnaraj, A.; Arun, A.; Kalaivani, S.S.; Maiyalagan, T.; Manikandan, A.; Balasubramanian, N.
Abstract: The Bismuth based Zinc metal oxide (ZnBi12 O20 ) nanorods were synthesized via single step solvothermal approach. The characterization of synthesized hybridized structure was done by several analysis such as X-ray diffraction (XRD), UV–Vis diffuse reflectance spectroscopy (UVvis–DRS), Fourier transform-infrared spectroscopy (FT–IR), Thermogravimetric analysis (TGA), Raman spectroscopy, Field-Emission scanning electron microscopy (FESEM), Energy dispersive analysis of X-rays (EDX), High-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy. The photocatalytic activity of ZnBi12 O20 and an incorporation of varying weight percentages of GO (1–4 wt %) into ZnBi12 O20 catalyst (GZBC) were analyzed under visible light irradiation by the degradation of an aqueous solution of Methylene blue (MB) and Methyl orange (MO) dye. Among various developed nanocomposites, 3 wt% GZBC reduced graphene oxide exfoliated nanocomposites has revealed the degradation efficiency as 96.04, 94.52% at 100 and 120 min for MB and MO respectively with enriched visible light absorption range. The photocatalytic property of 3 wt % reduced graphene oxide exhibits higher degradation behavior than that of other synthesized nano-composites.